PC based machine control monitoring and management system - Zhao, Guo Qing. (2008)
This thesis presents an actual case of HMI system. This system was used on the machine built for a customer of lens manufacturer. The customer wishes to have a small size machine developed for coating ophthalmic lenses designed to meet the needs of its prescription laboratories and some independent laboratories all over the world.